A floating body approach to Fefferman’s hypersurface measure - Barrett, David E. (MATHEMATICA SCANDINAVICA, 2006)
The floating body approach to affine surface area is adapted to a holomorphic context providing an alternate approach to Fefferman’s invariant hypersurface measure.